Hesychasm and the revival of monasticism in late Byzantine Cherson - Jaszajewa, Tatiana (Balcanica Posnaniensia. Acta et studia, 2009)
The turn of the 13th and 14th centuries in Byzantium was marked by cultural and spiritual prosperity, which historians refer to as the Palaeologus Renaissance. These processes also affected peripheral areas, including Cherson, the northern outpost of Byzantium. This was reflected in the spread of Hesychasm, a tradition of mystical silence and asceticism revived on Mount Athos. The aim of the study is to demonstrate the influence of Hesychasm and the ideas of Palamism on the revival of monasticism in late Byzantine Cherson. Archaeological data was used, written sources were compared, and the symbolic and iconographic significance of material monuments was analysed. The greatest attention was paid to the complex of cave and above-ground monasteries in the Cherson region. Their isolated location and organisation corresponded to the spirit of the Hesychast practice of ‘mental prayer’. This is indicated, among other things, by the early Christian symbolism used in the decor and ceramics. Key evidence of the influence of Palamism is also the signature of the Bishop of Cherson on the Tomos Hagiorytyczny document (1340, Hagioreitikos Tomos). The revival of monasticism in Cherson was part of a broad Eastern Christian movement associated with the strengthening of the spiritual foundations of late Byzantine society.